PROFESSIONAL COMPETENCE OF ENGLISH TEACHERS IN INDONESIA: A PROFILE OF EXEMPLARY TEACHERS - Mirjam Anugerahwati; Ali Saukah (Indonesian JELT, 2010)
This study was conducted to find out the profile of exemplary English teachers at secondary schools. Data were collected through observations, interviews, and questionnaires. The study was conducted in four towns, covering exemplary teachers in one senior high school and three junior high schools. The subjects were exemplary in terms of their active participation in the Teachers' Forum (MGMP), and their roles in the professional development of both themselves and their colleagues. This study was done mainly to find out (1) the professional competences of the exemplary teachers in each town and (2) how they achieve the competences. The collected data were analyzed qualitatively by the usual process of sorting, coding, and analyzing. The findings reveal that the subjects in three of the four towns have all the four competences (subject matter, pedagogical, social and personal competences), with the personal competence being the most influential in shaping them as professional and exemplary teachers.  From the findings a profile of the professional competences of the exemplary English teachers at secondary schools is developed. Keywords:      professional competence, exemplary teacher, profile.